Hardiness personality and job stress in policeman in the Police Office Tambun Bekasi - Wiwit Septiningsih; Iqbal, Muhammad (Psychology Journal of Mental Health, 2021)
This quantitative descriptive research aimed to find out the correlation between hardiness personality and job stress in policeman in the Police Office Tambun Bekasi. The questionaire was given to 75 respondents of the policeman in the police office Tambun Bekasi. The data obtained by job stress scale and hardiness personality scale. Analyzed by Spearman correlation technique from Product Momentl Pearson.With the hypothesis of hardiness personality has a negative and significantly relationship to the job stress of policeman in the police office Tambun Bekasi. The coefficient correlation (r) of -0,232 (p) < 0,05 showed that there are negative correlation between hardiness personality and job stress in policeman in the police office Tambun Bekasi. The result of one way Anova testing show that there is significant differentiation of work unit in all unit with job stress and hardiness personality. The high levels of hardiness personality has role to lower levels of job stress in policeman in the police office Tambun Bekasi.